Congenital Kyphosis And Kyphoscoliosis: The Natural History And Results After Surgery - Singh, Harwant (2000)
Congenital kyphosis and kyphoscoliosis are due to vertebral anomalies that are present at birth. These vertebral anomalies cause a deformity of the spine in the sagittal plane. If allowed to progress, this deformity can produce neural dysfunction due to bowstringing of the cord over the apex of the deformity. The goals of this study were to document the natural history of congenital kyphosis and kyphoscoliosis and to determine the stage at which the natural history should be interrupted by treatment. This was done by reviewing the medical records and radiographs of the spine of 1 12 consecutive patients. Sixty eight patients had a type-I kyphosis due to anterior failure of vertebral-body formation, twentyfour had a type-II kyphosis due to anterior failure of vertebral-body segmentation, and twelve had a type-III kyphosis due to a combination of anomalies. The deformities of the remaining eight patients could not be classified.